A REMARKABLE CLADONIACEAE FLORA AT INTERMEDIATE ELEVATION IN CHÁMEZA (CASANARE, COLOMBIA) (2014)
In Chámeza-Casanare (Colombia) in the subandean region (montane forest zone) at ca. 1200 m elevation a remarkable Cladoniaceae flora is discovered. Four observed species of the genus Cladonia (Cladoniaceae, Lichenized Fungi) are new records for Colombia: Cladonia macilentoides, C. scabriuscula, C. sipmanii and C. subdelicatula. This shows that suitable habitats for Cladoniaceae at intermediate elevations merit special interest in diversity studies.